Multi-parametric study of an eruptive phase comprising unrest, major explosions, crater failure, pyroclastic density currents and lava flows: Stromboli volcano, 1 December 2020–30 June 2021 - Calvari, S.; Di Traglia, F.; Ganci, G.; Bruno, V.; Ciancitto, F.; Di Lieto, B.; Gambino, S.; Garcia, A.; Giudicepietro, F.; Inguaggiato, S.; Vita, F.; Cangemi, M.; et al. (Frontiers in Earth Science, 2022)
Starting on December 2020, Stromboli volcano displayed an increasing eruptive activity, that on 19 May 2021 led to a crater-rim collapse, with pyroclastic density currents (PDCs) that spread along the barren NW flank, entered the sea and ran across it for more than 1 km. This episode was followed by lava flow output from the crater rim lasting a few hours, followed by another phase of lava flow in June 2021. These episodes are potentially very dangerous on island volcanoes since a landslide of hot material that turns into a pyroclastic density current and spreads on the sea surface can threaten mariners and coastal communities, as happened at Stromboli on 3 July and 28 August 2019. In addition, on entering the sea, if their volume is large enough, landslides may trigger tsunamis, as occurred at Stromboli on 30 December 2002. In this paper, we present an integration of multidisciplinary monitoring data, including thermal and visible camera images, ground deformation data gathered from GNSS, tilt, strainmeter and GBInSAR, seismicity, SO2 plume and CO2 ground fluxes and thermal data from the ground and satellite imagery, together with petrological analyses of the erupted products compared with samples from previous similar events. We aim at characterizing the preparatory phase of the volcano that began on December 2020 and led to the May-June 2021 eruptive activity, distinguishing this small intrusion of magma from the much greater 2019 eruptive phase, which was fed by gas-rich magma responsible for the paroxysmal explosive and effusive phases of July to August 2019. These complex eruption scenarios have important implications for hazard assessment and the lessons learned at Stromboli volcano may prove useful for other open conduit active basaltic volcanoes.